Protection of traditional knowledge: Deliberations from a transnational stakeholder dialogue between pharmaceutical companies and civil society organizations - Wolfgang van den Daele; Rainer Döbert; Achim Seiler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This report summarizes deliberations over the Protection of Traditional Knowledge held during a stakeholder dialogue process launched by the World Business Council for Sustainable Development (WBCSD) in 2001/2002. The dialogue process was designed to explore options of companies to address contested issues of intellectual property in their business strategies. To that end, companies were exposed to the concerns of stakeholders and urged to define responses to these concerns. The project involved major companies and transnational nongovernmental organizations as well as renowned experts in the field of intellectual property rights. This paper briefly sketches the project and the process of the Dialogue. The products of the process are the opinions, both concurring and dissenting, that the participants reached on the Protection of Traditional Knowledge, subsumed in the final report to the WBCSD that emerged from the project. This paper also reviews documents (Circulars) from the proceedings, which further illustrate the dynamics of the deliberations, and the range and direction of arguments exchanged by the participants. – – Das Diskussionspapier stellt die Ergebnisse dar, die im Rahmen eines vom World Business Council on Sustainable Development (WBCSD) initiierten Stakeholder Dialogs zum Thema Schutz des traditionellen Wissens erreicht worden sind. Ziel des Dialogs war es zu untersuchen, welche Optionen Unternehmen haben, öffentlichen Kritiken am geltenden Regime des geistigen Eigentums durch Anpassung ihrer Strategien Rechnung zu tragen. Beteiligt waren an dem Dialog Vertreter von großen pharmazeutischen Firmen und von transnational operierenden Nichtregierungsorganisationen, sowie Experten des Rechts des geistigen Eigentums. Das Diskussionspapier skizziert Charakter und Verlauf des Dialogverfahrens. Im Zentrum stehen die Ergebnisse zum Thema Schutz des traditionellen Wissens, wie sie in den vom World Business Council herausgegebenen Endberichts des Stakeholder Dialogs eingegangen sind – mit der Kennzeichnung der jeweils übereinstimmenden oder abweichenden Positionen der Teilnehmer. Es folgt eine kurze Diskussion dieser Ergebnisse. Im Anhang werden zentrale Dokumente des Verfahrens (Circulars) abgedruckt, die Einblick geben in die Dynamik der Verhandlungen und die Reichweite und Richtung der von den Teilnehmern ausgetauschten Argumente.
Keywords: 300; Immaterialgüterrechte; Stakeholder; Pharmazeutische Industrie; Nichtregierungsorganisation; Welt